Character Building of Students Through the Google Drive Media Assisted Story Method at Madrasah Ibtidaiyah Al Hidayah Kekatung Dente Teladas, Tulang Bawang Regency: Array (Journal of Research in Islamic Education, 2022)
The purpose of this study is (1) to explain and describe the steps of learning activities of moral aqidah using the story method in class IV MI Al Hidayah Kekatung, Dente Teladas District, Tulang Bawang Regency during the Covid 19 Pandemic. (2) To find out the process of character building of students in learning moral creed in class IV MI Al Hidayah Kekatung, Dente Teladas District, Tulang Bawang Regency during the Covid 19 Pandemic. (3) Knowing the role of the story method in shaping the character of students in learning moral creed in class IV MI Al Hidayah Kekatung, Dente Teladas District, District Tulang Bawang in the Covid 19 Pandemic. This type of research is a field research with a qualitative approach, the subjects of this research are the Principal, Deputy Head of Student Affairs, Akhlak Akidah Subject Teacher, and also students. Collecting data using interview, observation, and documentation techniques. The results of this study indicate that the steps of learning the moral aqidah with the story method must be carried out thoroughly so that learning runs optimally in accordance with expectations. These steps include preparation, implementation of learning and evaluation. The application of the storytelling method is carried out in stages starting from the teaching materials prepared in the lesson plans, then conveyed to students with great improvisational power of educators to change the positive behavior of students. The use of the Google Drive Media-assisted story method in learning moral creed in class IV MI Al Hidayah Kekatung, Dente Teladas District, Tulang Bawang Regency after an evaluation of students was carried out with very satisfactory results.